(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
Ecuador is a leading country in the agricultural sector, but it has deficiencies in the swine sector. This problem is worsening even more due to the lack of knowledge of the producers about the alternatives that can increase swine productivity. Therefore, the objective of this research was to evaluate the addition of efficient microorganisms in the feeding of pigs (Sus scrofa domesticus) in the growth and fattening stage. A Completely Randomized Experimental Design (C.A.D.) was used, evaluating 3 treatments plus 1 control treatment with 3 replicates. The different concentrations of efficient microorganism had a significant influence (p<0.05) on weight gain, determining that concentrations of 50 ml and 75 ml in growing pigs obtained a higher weight gain with values of 31.07 kg and 31.33 kg; while, when using concentrations of 300 ml (T1) in fattening pigs, a higher incidence in weight gain was obtained (47.62), being similar to the control treatment (T0). On the other hand, the different concentrations of ME for both growing and finishing pigs had no effect on the level of feed intake and feed conversion.